2006
DOI: 10.1016/j.jacc.2006.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Early Vascular Changes and Cardiovascular Risk Factors in Obese Children After a Six-Month Exercise Program

Abstract: The present study documented increased IMT, impaired endothelial function, and various elevated cardiovascular RF in young obese subjects. Regular exercise over 6 months restores endothelial function and improves carotid IMT associated with an improved cardiovascular risk profile in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
352
2
39

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(409 citation statements)
references
References 45 publications
(39 reference statements)
16
352
2
39
Order By: Relevance
“…These changes were not significant in comparison with improvements with diet and exercise interventions (27,28).…”
Section: Statisticsmentioning
confidence: 65%
See 1 more Smart Citation
“…These changes were not significant in comparison with improvements with diet and exercise interventions (27,28).…”
Section: Statisticsmentioning
confidence: 65%
“…One limitation to our study was the participation rate, which is, however, comparable with previous trials in obese children (27,28) and did allow good retention of children during the 24-week study period.…”
Section: Statisticsmentioning
confidence: 72%
“…27 Another study demonstrated that a 6 month regimen of diet alone or diet plus exercise training decreased carotid IMT in overweight children (BMI¼25 kg m À2 ±3; age between 9 and 12 years). 14 In this study, 1 year of intervention promoted a significant decrease in carotid IMT in obese adolescents (BMI¼36.50 kg m À2 ±4.99; age between 14 and 19 years).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study recommends reducing fat intake and increasing physical activity as strategies to minimize the impact of obesity on inflammatory disorders. 27 A similar interdisciplinary intervention should be considered as a potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A number of studies have reported higher IMT in obese compared with lean children and a reduction in IMT occurring with diet, physical activity and/or weight loss. [14][15][16] These factors, combined with the well-described tracking of obesity into adulthood, the greater clustering of cardiovascular risk factors with increasing levels of childhood obesity, including the presence of proinflammatory factors, [17][18][19] the presence of significant obesity-related morbidity in childhood, including fatty liver and psychosocial distress 20 and the important independent risk of adult obesity for cardiovascular disease, strongly argue for public health lifestyle interventions to target childhood overweight and obesity decades before the appearance of symptomatic cardiovascular disease.…”
mentioning
confidence: 99%